Non ohmic gigahertz conductivity in pressed pellets of ClO4 doped poly(3-methylthiophene) - Pawlicka, A.; Pereira, E. C.; Faria, R. M.; Bulhões, L. O. S.; Nascimento, O. R.; Walmsley, L. [UNESP] (Elsevier B.V., 1994)
ESR measurements In pressed pellets of <ClO(4)over bar> doped Poly(3-Methylthiophene)(P3MT) were performed at 10 K and 50 K after cooling the system slowly from room temperature to 110 K, quenching to 77 K and then to 10 K. ESR line asymmetry (A/B) as a function of microwave power was observed and 9.4 GHz conductivity was obtained from Dyson's theory. The data is discussed in terms of Charge-Density Wave (CDW) depinning. At 50 K the threshold electric field is estimated to be less than 1 V/cm. At 10 K a subtle pinning of the CDW was observed around 15 mW.
Keywords: A. Polymers; D. Electron-phonon interactions; E. Electron paramagnetic resonance